Malachi's vision of the temple : an emblem of eschatological hope (Malachi 3:1-5) and an economic centre of the community (Malachi 3:10-12) - Boloje, Blessing Onoriode (Journal for semitics, 2014)
This article shows how temples were viewed in biblical Israel and how the prophets understood the temple in their different contexts. The temple is emphasised as the abode of Yahweh by the prophets before the exile. During the exile, it is seen as a symbol of the reestablishment of the people as community of faith, and in the post-exilic era, the temple is conceived as an emblem of the restoration and revival of the people and as a representation of an eschatological hope. These prophetic conceptions of the temple are used by the prophets in their respective contexts to challenge people to move towards their aim. In keeping with these prophetic traditions, the article highlights the fact that in the book of Malachi the temple is discerned as an emblem of eschatological hope, wherein Yahweh's last judgment is determined and the triumph of his people is declared and granted (Malachi 3:1-5) and as an economic centre of the community (Malachi 3:10-12). The consistency of Malachi's vision validates similar prophetic formulae and theological themes.